Perancangan Aplikasi Pengolahan Data Nilai Siswa Berbasis Website - Widiatry, Widiatry; Cordias, Gebri Meizeri (Universitas Palangka Raya, 2022)
Education is very important for the future of Indonesia's young generation today. In order to give birth to a better Indonesian golden generation, teaching staff must have a benchmark of student values in the development of student values and activeness which is commonly called a report card. The lack of application of technology as a medium for managing report cards for teachers is still considered ineffective and also inefficient in terms of time. Besides that, there are many problems regarding the difficulty of parents to check report cards because they have very busy activities and busyness in work matters besides that teachers need special time to meet and discuss in preparing report cards so we need a system that can be accessed anywhere and anytime. Report cards are one of the important documents for students. So it is necessary to be careful when storing it. Filling out a report card is also a troublesome thing for teachers. The teacher must fill in the lesson values as many students as there are in his class. Of course it is not efficient. Then a website-based report card value processing information system was created called E-Raport or Electronic Reportport. This system was developed using Sublime Text software, PHP, XAMPP, and MySQL database. This system is expected to make it easier for teachers to fill in value data and students in checking and storing report cards.